Citra Qatar pada ISU LGBTQ Pasca Piala Dunia 2022: Studi Netnografi di X - Amelia Rolanda Prasetya (Fakultas Ilmu Sosial dan Ilmu Politik, 2026)
Following the 2022 World Cup, Qatar received numerous negative comments on X, particularly concerning the LGBTQ community. The post-event phase is a crucial period for understanding the continuity of Qatar's image in digital spaces, as prior studies have largely focused on the period during the tournament itself. This study employs a qualitative method with a passive netnographic approach on X. A total of 311 tweets related to the LGBTQ issue and freedom of expression were analyzed, collected through advanced search covering the period from December 2022 to December 2023. The analysis integrates Kriyantono's (2017) public opinion concept with Buhmann's (2017) country image concept, focusing on the normative dimension. This study finds that international public opinion regarding Qatar's LGBTQ issue was constructed through the contestation of three narratives: a critical narrative framing Qatar as violating universal human rights, a defensive narrative framing restrictions on LGBTQ symbols as an assertion of cultural and religious sovereignty, and a whataboutism narrative questioning the moral consistency of Qatar's critics. These findings indicate that Qatar's normative image in the digital space was not uniformly constructed, but rather emerged from a contestation of values between the universality of human rights, cultural relativism, and the moral legitimacy of the actors involved in the digital discourse following an international mega-event.
:: Finalisasi file repositori 23 Juli 2026_Kurnadi
Keywords: Human Rights; Country Image; Qatar; Public Opinion; LGBTQ